2005
DOI: 10.1038/sj.bjc.6602383
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[b]thiophenesulphonamide 1,1-dioxide derivatives inhibit tNOX activity in a redox state-dependent manner

Abstract: Benzo [b]thiophenesulphonamide 1,1-dioxide (BTS) derivatives are strong cytotoxic agents that induce reactive oxygen species (ROS) overproduction and apoptosis in tumour cells. Although the precise origin of BTS-induced ROS is not known, a clear correlation between their cytotoxic effect and ability to inhibit a tumour-associated NADH oxidase (tNOX) activity of the plasma membrane has been described. To analyse the putative implication of tNOX in BTS-induced ROS generation, in this work we have synthesised and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Aromatic sulfonamide derivatives exhibit a range of bioactivities, including anti-angiogenic (Funahashi et al 2002;Semba et al 2004), anti-tumor (Semba et al 2004;Sławínski and Gdaniec 2005), antiinflammatory and analgesic (Chen et al 2005), anti-tubercular (Gadad et al 2004), anti-glaucoma (Agrawal et al 2004), anti-HIV (Yeung et al 2005), cytotoxic (Encío et al 2005), antimicrobial (Nieta et al 2005) and antimalarial (Domínguez et al 2005) agents. The synthesis of metal sulfanilamide compounds had received much attention due to the fact that sulfanilamides were the first effective chemotherapeutic agents to be employed for the prevention and cure of bacterial infections in humans (Bult 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic sulfonamide derivatives exhibit a range of bioactivities, including anti-angiogenic (Funahashi et al 2002;Semba et al 2004), anti-tumor (Semba et al 2004;Sławínski and Gdaniec 2005), antiinflammatory and analgesic (Chen et al 2005), anti-tubercular (Gadad et al 2004), anti-glaucoma (Agrawal et al 2004), anti-HIV (Yeung et al 2005), cytotoxic (Encío et al 2005), antimicrobial (Nieta et al 2005) and antimalarial (Domínguez et al 2005) agents. The synthesis of metal sulfanilamide compounds had received much attention due to the fact that sulfanilamides were the first effective chemotherapeutic agents to be employed for the prevention and cure of bacterial infections in humans (Bult 1983).…”
Section: Introductionmentioning
confidence: 99%
“…One approach is to reduce ROS levels in tumors to a more physiological concentration, which would be predicted to retard cancer progression [133]. This can be achieved by preventing ROS and RNS production with enzyme inhibitors such as allopurinol, N G -monomethyl-L-arginine and benzo [b]thiophenesulphonamide derivatives, which inhibit xanthine oxidase, NOS and NADPH oxidase respectively [134][135][136]. Enzyme mimics can also be used to target tumors and transition metal complexes with organic ligands such as the phorphyrins, salens and salicylaldehydes can exhibit SOD and CAT activity [135], while organochalcogens can mimic GPx [134].…”
Section: Discussionmentioning
confidence: 99%
“…De Luca et al [9] showed that the NAD + /NADH and/or CoQ/CoQH 2 ratios from plasma membrane electron transport system may modulate in a mutual manner two enzymes, sphingomyelinase and sphingosine kinase, possibly heading to G 1 arrest and apoptosis. Furthermore, strong cytotoxic agents benzo[b]thiophenesulphonamide 1,1dioxide (BTS) derivatives have been found to inhibit tNOX activity and lead to apoptosis induction in cancer cells through generation of reactive oxygen species [10]. However, the detailed mechanism for tNOX inhibitors to induce apoptosis of cancer cells remains ambiguous.…”
Section: Discussionmentioning
confidence: 99%